Design of wideband, low loss, high power waveguide couplers and transitions for implementation in power combiners and dividers - Krüger, J. C.(Jacob Carel) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Ing.) -- University of Stellenbosch, 1998.